2002
DOI: 10.1007/s00330-002-1363-9
|View full text |Cite
|
Sign up to set email alerts
|

Low-field magnetic resonance imaging for intraoperative use in neurosurgery: a 5-year experience

Abstract: The aim of this study was to evaluate the feasibility and point out the indications of intraoperative MR imaging in neurosurgical procedures. The MR imaging was performed using a 0.2-T scanner which was located in a radiofrequencyshielded operating theater. Three major setups for intraoperative imaging were possible: inside the scanner; at the 5-Gauss line; or in an adjacent operating theater. Additionally, in lesions adjacent to eloquent brain areas microscope-and pointer-based neuronavigation with integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(7 citation statements)
references
References 58 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…46,54,62,63 Initial studies evaluating the usefulness of iMRI for surgical removal of brain tumours have been confined largely to intrinsic lesions, and have indicated that surgeons continued resection 38% of the time after iMRI assessment of the completeness of resection following their initial attempt, which underscores the importance of intraoperative imaging in this patient population. 64 The literature suggests at least level 2 evidence supports the utility of iMRI in improving the extent of resection, survival and quality of life in patients with glioma. 62,65 Whether this therapeutic value will extend to metastatic brain tumours remains to be determined; however, as iMRI technology becomes more common, this issue will probably be resolved.…”
Section: Brain Metastases—surgical Managementmentioning
confidence: 99%
“…46,54,62,63 Initial studies evaluating the usefulness of iMRI for surgical removal of brain tumours have been confined largely to intrinsic lesions, and have indicated that surgeons continued resection 38% of the time after iMRI assessment of the completeness of resection following their initial attempt, which underscores the importance of intraoperative imaging in this patient population. 64 The literature suggests at least level 2 evidence supports the utility of iMRI in improving the extent of resection, survival and quality of life in patients with glioma. 62,65 Whether this therapeutic value will extend to metastatic brain tumours remains to be determined; however, as iMRI technology becomes more common, this issue will probably be resolved.…”
Section: Brain Metastases—surgical Managementmentioning
confidence: 99%
“…This intraoperative movement of brain tissue is in the literature usually referred to as brain shift. The magnitude of such a shift can reach up to 20 mm, and the resection of big lesions during surgery can increase the deformation of the surrounding brain structures even up to 50 mm (1)(2)(3) . Such a considerable movement of tissue movement causes a significant decrease in accuracy of commercially available neuronavigation systems which are based on preoperatively acquired data only.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, various imaging modalities have been considered, e.g. ultrasound (US) (4,5) , x-ray computed tomography (CT) (6) and magnetic resonance imaging (MRI) (1,2,7) . Especially, applying intraoperative MR supported by a navigation system offers a very convenient solution to the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experience with open MR systems and with MRI radiation therapy simulators[474865] suggest that this is readily achievable with a MR system with a relatively low field strength around 0.2T. The present system is based on a field strength of 0.25 T. The low field strength would be advantageous as it reduces image distortion due to an object (i.e.…”
Section: Radiation Delivery Systemmentioning
confidence: 99%